2020
DOI: 10.1177/0266242620927312
|View full text |Cite
|
Sign up to set email alerts
|

Women on the edge of a breakthrough? A stereotype threat theory of women’s angel investing

Abstract: The extent to which women participate in the angel investment market has become an important topic of research and policy interest. Based on UK survey data, we demonstrate that there are systematic but not unequivocal differences between women and men investors on a number of key investor and investment characteristics. We also report indicative evidence that members of women-only networks do differ from women who join mixed networks. Drawing on these results, we develop a stereotype threat theory per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 149 publications
(206 reference statements)
1
7
0
Order By: Relevance
“…Two types of learning experience can be identified within this group of informal learners (Table 2): learning from the investment opportunity is typically associated with negative learning outcomes (e.g. long times to exit, people not being trustworthy, greedy entrepreneurs), supporting prior research on investors’ risk perceptions (Harrison and Mason, 2017); learning about being an angel is where participants learned more about the skills required to be an angel investor (e.g. patience, assertiveness, scepticism).…”
Section: Resultssupporting
confidence: 63%
“…Two types of learning experience can be identified within this group of informal learners (Table 2): learning from the investment opportunity is typically associated with negative learning outcomes (e.g. long times to exit, people not being trustworthy, greedy entrepreneurs), supporting prior research on investors’ risk perceptions (Harrison and Mason, 2017); learning about being an angel is where participants learned more about the skills required to be an angel investor (e.g. patience, assertiveness, scepticism).…”
Section: Resultssupporting
confidence: 63%
“…The review revealed that empirical evidence was not sufficient in supporting such conclusion and that the cultural and contextual influences also contribute to the gender differences in risk-taking behavior. Harrison et al (2020) also found that this kind of stereotype threat exerts negative influences on women investors, depressing their investment performance.…”
Section: Resultsmentioning
confidence: 89%
“…Cluster #4 is labeled as gender difference, which means that the investigation of the effects of gender on FDM have attracted researchers’ attention. This cluster includes 28 articles and the top three most cited papers are Yordanova and Alexandrova-Boshnakova (2011) , Nelson (2015) , Harrison et al (2020) . Yordanova and Alexandrova-Boshnakova (2011) administered a survey to 382 Bulgarian owner-managers of business to explore the gender differences in these businesses owners’ decision making under risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors are an extremely common project feature previously analysed in many business areas, such as audits, sales or credit. In the for-profit sector, risk management is regularly applied during investment projects, for instance, through the use of due diligence mechanisms prior to investing in order to detect vulnerabilities that could contribute to future damaging contingencies (Harrison & Mason, 2017). The field of risk management has also gained increasing importance in public sector management (Bracci, Tallaki, Gobbo & Papi, 2021).…”
Section: Introductionmentioning
confidence: 99%